Polyhydroxyurethane and methods for making and using same
By using cyclic carbonate and amine reactants at high temperatures to form hydroxide-containing ethylene bonds, and introducing reversible phenol bonds and epoxy bonds, the problem of difficult development of thermosetting glue forms of PHU materials in the prior art is solved, and high-performance, repeatable processing and fully recovered PHU materials are achieved.
Patent Information
- Application Number
- JP2024549188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-23
- Filing Date
- 2023-01-23
- Publication Date
- 2025-04-22
AI Technical Summary
It is difficult to develop high-performance, repeatable processing and recycling polyol urea (PHU) materials, especially their thermosetting forms.
By using aminolysis reaction of cyclic carbonate and amine reactants at high temperatures, a PHU material containing hydroxide ethylene bonds is formed, and its repeatability and mechanical properties are improved by the introduction of reversible phenol bonds and epoxy bonds.
It realizes the high temperature stability, chemical durability, good adhesion and wear resistance of PHU materials, and has the advantages of repeatable processing and full recycling.
Smart Images

Figure 2025512664000001_ABST
Abstract
Description
[Technical field]
[0001] (Related Applications) This application claims priority to U.S. Provisional Patent Application No. 63 / 322,758, filed March 23, 2022, the contents of which are incorporated herein by reference in their entirety for all purposes.
[0002] (Statement Regarding Federally Funded Research) This invention was made with Government support under Grant No. DE-SC0021869 awarded by the U.S. Department of Energy. The U.S. Government has certain rights in this invention. [Background technology]
[0003] (background) Carbon dioxide (CO2) is the primary greenhouse gas produced by the consumption of fossil fuels and other human activities. Billions of tons of CO2 taken from the atmosphere can be used as a feedstock to make plastics.
[0004] Although the chemical fixation approach of converting CO2 into valuable chemicals may not alone have a significant impact on reducing atmospheric CO2 levels, it has been considered a viable and attractive way to chemically capture and recycle CO2.
[0005] The conversion of CO2 into recyclable plastics can contribute to CO2 sequestration and facilitate the transition from current fossil fuel-based plastic materials to more sustainable materials for future generations.
[0006] Polyurethane (PU) is the most widely used plastic material with an annual production of nearly 24 million metric tons in 2020, which accounts for about 7% by weight of all plastics production. PU exists in both thermoplastic and thermoset forms and has been used in a wide range of end-user applications (e.g., heat-storing foams, adhesives, architectural coatings, packaging, and medical devices). However, its production has been heavily dependent on phosgene-derived isocyanates. Due to the high toxicity of the chemicals used in its production, the increasing demand for PU has raised serious health and environmental concerns. Approximately half of the PU production volume is a crosslinked thermoset with a permanently fixed morphology, which cannot be reprocessed and repaired. As a result, a large amount of hard-to-recycle PU (including scrap from post-consumer products as well as post-industrial products) ends up in landfills, which amount to nearly 10% of the total PU production.
[0007] Polyhydroxyurethane (PHU) is a non-isocyanate PU derivative that can be prepared from cyclic carbonates, which are less toxic and more environmentally friendly. Unlike PU, PHU does not have the disadvantages of biuret and allophanate, and contains free hydroxyl groups that can form intramolecular and intermolecular hydrogen bonds. Therefore, PHU generally exhibits higher thermal stability, chemical resistance, and improved adhesion and abrasion resistance than conventional PU.
[0008] Cyclic carbonates (starting materials for PHU) can be formed through the cycloaddition of CO2 to epoxides, which is a convenient and efficient method for chemical fixation of CO2. Such a reaction has many advantages, including, for example: (1) CO2 is directly used as an abundant, cheap, and renewable C1 feedstock, and the process does not involve the energy-intensive reduction of CO2; (2) the process is 100% atom economical; (3) the reaction can be solvent-free; and (4) the reaction is thermodynamically favorable, since the high free energy of epoxides is balanced with the high thermodynamic stability of carbon dioxide.
[0009] The development of PHU has been limited primarily to thermoplastic forms with low molecular weights and poor mechanical properties. Thermoset forms of PHU that are reprocessable and recyclable are rarely found. Summary of the Invention [Means for solving the problem]
[0010] (overview) The present disclosure provides methods for producing and using PHUs and composite materials incorporating PHUs. These polymers and composite materials are moldable, remoldable, and recyclable.
[0011] In one embodiment, the PHU is a polymer comprising hydroxyurethane bonds formed from the reaction between cyclic carbonate monomers and amine monomers.In one embodiment, the molar ratio of hydroxyurethane bonds is greater than 50% among all the bonds between monomers.In another embodiment, the molar ratio of hydroxyurethane bonds is greater than 60% or 70% among all the bonds between monomers.
[0012] In one embodiment, the PHU is prepared from at least one polyvalent cyclic carbonate and at least one polyvalent diamine monomer in amounts such that the molar equivalent ratio between the total cyclic carbonate groups and the total amine groups in the reaction system is about 1:1 (i.e., about 1:1 cyclic carbonate:amine).
[0013] In another embodiment, the PHU comprises polyvalent cyclic carbonate or polyvalent amine monomers as crosslinkers.
[0014] According to certain embodiments of the present disclosure, polycyclic carbonate monomers can be prepared through [3+2]CO2 insertion into the corresponding epoxy precursors at elevated temperatures in the presence of a catalyst (Figure 1A, Figure 3A, Figure 3B). Various metal complexes, metal halides, ionic liquids, ammonium, or phosphonium salts can be used as the catalyst. Examples of the catalyst include tetrapropylammonium bromide (TPAB), Ti(O i Examples of suitable iodides include, but are not limited to, 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU and I2), and tetrabutylammonium iodide (TBAI).
[0015] In some embodiments, simple and inexpensive aliphatic or aromatic based epoxides with various reactivities, flexibility, and steric effects can be converted into cyclic carbonates. Examples of epoxides include, but are not limited to, diglycidyl ether of bisphenol A (DGEBA), 4,4'-methylenebis(N,N-diglycidylaniline) (TGMDA), biocompatible glycol diglycidyl ether (PEGDE), epoxidized vegetable oils (e.g., epoxidized soybean oil (ESBO)), and limonene dioxide (LEP) (Figure 2A).
[0016] In one embodiment, a method for converting DGEBA to the corresponding cyclic carbonate (DGEBA-CO2) is provided, using a combination of tetrapropylammonium bromide (TPAB) and Ti(OiPr)4 as a catalytic system at elevated temperatures (80°C-150°C). Quantitative yields (95%-100%) of the cyclic carbonate can be obtained under optimal CO2 pressures (e.g., 100 Psi-700 Psi, or 200 Psi-600 Psi, or 300 Psi-500 Psi) and reaction temperatures of 80°C-150°C, or 80°C-140°C, 100°C-150°C, or 80°C-120°C.
[0017] In one aspect, the present invention provides a method for the polymerization of cyclic carbonates through aminolysis at elevated temperatures (80° C.-150° C.) (FIG. 1A). Examples of amines that may react with cyclic carbonates include, but are not limited to, hydrazine, diethylenetriamine (DETA), isophoronediamine (IPDA), tris(2-aminoethyl)amine (TREN), 4,4'-oxydianiline (ODA), and Priamine (a 100% bio-based diamine), and bis(3-aminopropyl) terminated poly(dimethylsiloxane) (molecular weight 500-8000) (FIG. 2B).
[0018] In some embodiments, common side reactions (e.g., amine carbonation, urea formation, amidation reactions, or oxazolidinone synthesis) may be prevented at reaction temperatures below 130° C. Catalyst, solvent, temperature, reaction time, and stoichiometric ratio of cyclic carbonate to amine are important factors to promote polymerization and reduce side reactions. Solvent-free polymerization or melt-phase reactive extrusion in a twin-screw kneading extruder may be possible.
[0019] In one embodiment, the present invention relates to the incorporation of epoxy resins to adjust the properties of PHU. The molar ratio between epoxide groups and cyclic carbonate groups in the monomer mixture can be in the range of 1% to 30%, or 5% to 25%, or 10% to 20%.
[0020] In one embodiment, the present invention relates to the incorporation of reversible imine bonds as additional dynamic covalent bonds to enhance the reprocessability of PHU at relatively low temperatures (e.g., 80° C.-140° C., or 90° C.-130° C., or 100° C.-130° C., or 80° C.-120° C.). The molar ratio between imine bonds and carbamate bonds can be in the range of (1%-30%), or 5%-25%, or 10%-20%.
[0021] In one embodiment, a method for preparing the PHU polymer comprises the steps of: a) combining a molten mixture of at least one polyvalent cyclic carbonate monomer and at least one polyvalent amine monomer in the presence or absence of a solvent and a base catalyst; b) heating the mixture of step a) to a temperature between 80°C and 250°C until all of the volatile materials have evaporated and polymerization is complete; c) allowing the polymer of step b) to cool to a temperature in the vicinity of 20°C to 25°C.
[0022] In one embodiment, a method for preparing a PHU containing a dynamic imine bond comprises the steps of: a) combining a molten mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer in the presence or absence of a solvent and a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until all of the volatile materials have evaporated and polymerization is complete; c) allowing the polymer of step b) to cool to a temperature in the vicinity of 20° C. to 25° C.
[0023] In another embodiment, a method for preparing a PHU polymer comprising an epoxy resin comprises the steps of: a) combining a molten mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent epoxide monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer in the presence or absence of a solvent and a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until all of the volatiles have evaporated and polymerization is complete; c) allowing the polymer of step b) to cool to a temperature in the vicinity of 20° C. to 25° C.
[0024] In some embodiments, the present invention relates to reversible carbamoylation (FIG. 1B), which occurs through the exchange of carbamate groups with free pendant hydroxyl groups at elevated temperatures in the absence or presence of base catalysts, examples of which include, but are not limited to, triazabicyclodecene (TBD) or 4-dimethylaminopyridine (DMAP). In one aspect, the disclosed PHU contains both free hydroxyl groups and urethane bonds, which undergo carbamoylation to provide its malleability and reworkability.
[0025] In one aspect, the present invention relates to the malleability and reworkability of PHU. When heat and pressure are applied to the PHU, the PHU can undergo reversible carbamoylation to adapt to those external stimuli (here heat and pressure) by releasing its stress. Thus, the crosslinked PHU can be reworkable and reshapeable when the reversibility of carbamoylation is activated at high temperatures of 200°C to 270°C, or 220°C to 260°C, or 230°C to 250°C.
[0026] In one embodiment, the present invention relates to the incorporation of epoxy resins to improve the mechanical properties of PHUs. The molar ratio of epoxide groups to cyclic carbonate groups in the monomer mixture can be in the range of 1% to 10%, or 3% to 8%, or 4% to 6%.
[0027] In one embodiment, the present invention relates to the incorporation of reversible imine bonds as additional dynamic covalent bonds to enhance the reprocessability of PHU at relatively low temperatures (e.g., 80° C.-140° C., or 90° C.-130° C., or 100° C.-130° C., or 80° C.-120° C.). The molar ratio of imine bonds to carbamate bonds can be in the range of 1%-10%, or 3%-8%, or 4%-6%.
[0028] In one embodiment, the PHU polymer can be reprocessed at least once through transitions between a non-malleable state and a malleable state and between a malleable state and a non-malleable state upon exposure to a range of temperatures, a rate of carbamoyl group transfer imparts the polymer with a malleable state, and the PHU polymer includes a base catalyst that results in a decrease in the transition temperature compared to the PHU polymer in the absence of the catalyst. In another embodiment, the transition temperature is from about 80° C. to about 250° C., or from 120° C. to 200° C., or from 150° C. to about 180° C.
[0029] In one embodiment, the present invention provides for recycling of the PHU through depolymerization (FIG. 1C). The depolymerization process includes: a) contacting the PHU polymer with a liquid containing at least molecules having a primary hydroxy or amine moiety in the presence or absence of a base; and b) substantially dissolving the polymer in the liquid of step a) to form a polymer solution; and c) using the polymer solution from step b) to prepare a PHU polymer.
[0030] In another embodiment, the process of recycling the PHU through depolymerization includes: a) contacting the PHU polymer with a liquid containing at least molecules with primary hydroxy or amine moieties in the presence or absence of a base; and b) completely dissolving the polymer in the liquid of step a) to convert it into a small molecule; and c) purifying the small molecule of step b) to obtain a pure small molecule chemical that can be used to produce other materials.
[0031] In another embodiment, the crosslinked PHU can be combined with various forms of reinforcing additives, including talc, clay, carbon fiber (new, recycled, woven, chopped, or milled), natural fibers (hemp, flax, etc.), graphene, carbon black, glass fiber, or other additives (e.g., flame retardants, surface modifiers, dyes, pigments, and mold release agents). The amount of reinforcing additives can be 5%-70%, and the amount of other additives can be preferably <5%.
[0032] In one embodiment, a method for preparing a composite material includes: a) immersing the toughening additive in a molten mixture of at least one polyvalent cyclic carbonate monomer and at least one polyvalent amine monomer in the presence or absence of a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until polymerization is complete; c) pressing the heated composite of step b) into a mold; and d) allowing the heated composite of step c) to cool to a temperature below its transition temperature.
[0033] In one embodiment, a method for preparing a composite material includes: a) immersing the toughening additive in a molten mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer, with or without a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until polymerization is complete; c) pressing the heated composite of step b) into a mold; and d) allowing the heated composite of step c) to cool below its transition temperature.
[0034] In one embodiment, a method for preparing a composite material includes: a) immersing the fibrous or non-fibrous filler material in a solution of a mixture of at least one polyvalent cyclic carbonate monomer and at least one polyvalent amine monomer in a solvent with or without a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until all the volatiles have evaporated and the polymerization is complete; c) pressing the heated composite of step b) into a mold; and d) allowing the heated composite of step c) to cool to a temperature below its transition temperature.
[0035] In one embodiment, a method for preparing a composite material includes: a) immersing the fibrous or non-fibrous filler material in a solution of a mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer in a solvent with or without a base catalyst; b) heating the mixture of step a) to a temperature between 80° C. and 250° C. until all the volatiles have evaporated and the polymerization is complete; c) pressing the heated composite of step b) into a mold; and d) allowing the heated composite of step c) to cool to a temperature below its transition temperature.
[0036] In one aspect, the invention relates to the processing of a fiber reinforced composite (FRC) sheet produced using a PHU and fibers through a heat press, comprising: a) heating the FRC sheet above its transition temperature between a malleable and non-malleable state; b) forcing the sheet into a rigid die to produce a composite sheet that conforms to the die; c) allowing the composite to cool below its transition temperature. Complete stress relaxation in the PHU matrix allows the FRC sheet to retain its deformed shape even after the compression is removed.
[0037] In an embodiment, the PHU composite can be reprocessed at least once through transitions between a non-malleable state and a malleable state and between a malleable state and a non-malleable state upon exposure to a range of temperatures, a rate of carbamoyl group transfer imparts the polymer with a malleable state, and the PHU polymer can include a base catalyst that results in a decrease in the transition temperature compared to the PHU polymer in the absence of the catalyst. In one embodiment, the transition temperature is from about 80° C. to about 250° C.
[0038] In one embodiment, the present invention provides a method for recycling the composite material, the method comprising: a) contacting the composite material with a liquid containing at least molecules having primary hydroxy moieties in the presence or absence of a base; and b) substantially dissolving the composite material in the liquid of step a); and c) separating the resulting solution from the fibrous or non-fibrous filler material; and d) using the polymer solution from step c) to prepare a PHU polymer; and e) using the filler material from step c) to prepare a composite material.
[0039] In another aspect, the present invention provides a method for recycling the composite material, the method comprising: a) contacting the composite material with a liquid comprising at least molecules having primary hydroxy or amine moieties in the presence or absence of a base; and b) substantially dissolving the composite material in the liquid of step a); and c) separating the resulting solution from the fibrous or non-fibrous filler material; and d) purifying the solution from step c) to obtain small molecule chemicals; and e) preparing a composite material using the filler material from step c).
[0040] The above embodiments can provide high performance, recyclable and malleable PHU thermosets from inexpensive monomers prepared using CO2. The PHU thermosets are stable under a variety of harsh conditions, including exposure to acids. The presence of inherent hydroxyl groups can enable dynamic bond exchange via carbamoyl transfer, endowing the crosslinked PHUs with unique characteristics, including malleability, reworkability, and recyclability. They can be completely degraded through depolymerization into monomers or other value-added small molecules, allowing for recycling or upcycling of all of their chemicals.
[0041] The above embodiment can provide a solvent-free synthesis of cyclic carbonates and their polymerization that can be easily scaled up on an industrial scale. Depending on the monomer structure, PHUs with rubber-like elastomeric or thermoplastic-like properties can be suitable as 3D printing materials, or thermoset-like plastics can have mechanical properties comparable to commonly used epoxy thermosets.
[0042] The above embodiments may provide a recyclable, conductive FRC when carbon fibers and conductive fillers (e.g., conductive carbon black or conductive graphene) are used as reinforcing additives and a PHU is used as the matrix.
[0043] Features and steps from any of the disclosed embodiments can be used in combination with each other without limitation. For example, any of the compositional limitations described with respect to one embodiment can be present in any of the other embodiments described. Furthermore, other features and advantages of the present disclosure will become apparent to those skilled in the art through the following detailed description and the accompanying drawings. [Brief description of the drawings]
[0044] [Figure 1A]FIG. 1A shows a schematic diagram of the process for the formation of polyhydroxyurethane from an epoxide via CO2 addition to form a cyclic carbonate followed by aminolysis to form a polyhydroxyurethane.
[0045] [Figure 1B] FIG. 1B shows a schematic diagram of the carbamoylation dynamic exchange process.
[0046] [Figure 1C] FIG. 1C shows a schematic diagram of the PHU decomposition process through carbamoyl transfer in alcohol.
[0047] [Figure 1D] FIG. 1D shows the composition of various PHUs, including hydroxyurethane, imine, and -N-CH2-C(OH)- bonds.
[0048] [Figure 2A] 2A and 2B show examples of epoxide and amine structures that can be used in cyclic carbonate formation and PHU polymer formation. [Figure 2B] Same as above.
[0049] [Figure 3A] Figure 3A shows the synthesis of PHU-containing polymers (PHU, PHU-PI, and PHU-PI-epoxy) from DGEBA-CO2. DGEBA-CO2 can be synthesized from DGEBA through CO2 insertion under the combined catalysis of Ti(OiPr)4 and TPAB.
[0050] [Figure 3B] FIG. 3B shows the nuclear magnetic resonance (NMR) spectra of DGEBA and the crude product obtained after CO2 insertion into DGEBA (DGEBA-CO2).
[0051] [Figure 3C]FIG. 3C shows a representative tensile stress-strain curve of a PHU polymer containing approximately 10 mol % imine linkages.
[0052] [Figure 4] Figure 4 shows a schematic diagram of the decomposition of cross-linked PHU generated from DGEBA-CO2 and TREN. The PHU can be decomposed after immersion in EtOH with stirring at 100 °C for 8 h in the presence of K2CO3. The decomposition products are DGEBA-4OH and 3Cbm-TREN. 3Cbm-TREN can be further converted to 3Me-TREN.
[0053] [Figure 5A] Figure 5A shows a schematic diagram of the formation of PHU-based carbon fiber reinforced composites (PHU-CFRCs) through in situ polymerization of DGEBA-CO2 and TREN in the presence of a carbon fiber fabric sheet, and an optical image of the carbon fiber composite is also shown.
[0054] [Figure 5B] FIG. 5B shows the reshaping of PHU-CFRC through simple application of heat and external force.
[0055] [Figure 5C] Figure 5C shows the recycling of PHU-CFRCs in ethanol: undamaged carbon fibers can be recovered from the decomposition solution.
[0056] [Figure 6] FIG. 6 shows the production of conductive carbon fiber reinforced composites (CFRC) using recycled milled carbon fibers and conductive carbon black (super C45). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0057] The drawings are included to provide a better understanding of the invention, are not intended to limit the scope, but are intended to provide exemplary illustrations.
[0058] DETAILED DESCRIPTION OF VARIOUS EMBODIMENTS It should be understood that the present disclosure is not limited to the specific embodiments and methods described below, as specific components and / or conditions may vary. Moreover, the terminology used herein is used only for the purpose of describing specific embodiments, and is not intended to be limiting in any manner.
[0059] Except in the examples, or where otherwise expressly stated, all numerical quantities in this description indicating amounts of materials or reaction conditions and / or conditions of use should be understood to be modified by the term "about" in describing the broadest scope of this disclosure.Also, unless expressly stated to the contrary, the description of components in chemical terms refers to the components when added to any combination specified in the description, and does not necessarily exclude chemical interactions between the components of the mixture once mixed; the first definition of an acronym or other abbreviation applies to all subsequent uses of the same abbreviation in this specification; unless expressly stated to the contrary, measurements of properties are determined by the same techniques as those previously or subsequently referenced for the same property.
[0060] It should also be noted that as used in this specification and the appended claims, the singular forms "a," "an," and "the" can include plural referents unless the context clearly dictates otherwise. For example, reference to a singular component is intended to include the plural components.
[0061] Unless otherwise defined, all technical and scientific terms used herein generally have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. Generally, the nomenclature and laboratory procedures in organic and polymer chemistry used herein are those well known and commonly used in the art.
[0062] As used herein, the term "polymerization" or "crosslinking" refers to at least one reaction that consumes at least one functional group in a monomer, oligomer, or polymer to generate at least one chemical bond between at least two separate molecules (e.g., an intermolecular bond), at least one chemical bond within the same molecule (e.g., an intramolecular bond), or any combination thereof. A polymerization or crosslinking reaction may consume between about 0% and about 100% of the at least one functional group available in the system. In an embodiment, polymerization or crosslinking of at least one functional group results in consumption of about 100% of the at least one functional group. In another embodiment, polymerization or crosslinking of at least one functional group results in consumption of less than about 100% of the at least one functional group.
[0063] As used herein, the term "high temperature" refers to a temperature above room temperature (room temperature is typically between 20° C. and 25° C.).
[0064] Disclosed herein is a catalyst for CO2 insertion into epoxides to form cyclic carbonates. A wide variety of polycyclic carbonates can be prepared from epoxides through CO2 insertion. By way of example, the catalyst can include, but is not limited to, a combination of Ti(OiPr)4 and tetrapropylammonium bromide, or a combination of Ti(OiPr)4 and tetrabutylammonium bromide.
[0065] A composition comprising PHU is disclosed herein. In an embodiment, the PHU can be prepared from a divalent cyclic carbonate monomer, a diamine monomer, and a multivalent crosslinking agent. The crosslinking agent includes a multivalent cyclic carbonate monomer, a multivalent aldehyde monomer, or a multivalent amine monomer. Many diamines and triamines are readily available, making PHU an accessible class of polymer to synthesize. Non-limiting examples of epoxide precursors and amine monomers that can be used to generate the PHU of the present disclosure are shown in Figures 2A-2B.
[0066] In one embodiment, the preparation of linear PHUs involves the combination of appropriately shaped divalent cyclic carbonate and diamine monomers. In a non-limiting aspect, the preparation of crosslinked PHUs further involves the use of trivalent, tetravalent or polyvalent cyclic carbonate monomers, or the use of trivalent, tetravalent or polyvalent amine monomers.
[0067] In one embodiment, the preparation of crosslinked PHUs involves the combination of appropriately shaped divalent cyclic carbonate, divalent aldehyde and diamine monomers. In non-limiting aspects, the preparation of such crosslinked PHUs (PHU-PIs) further involves the use of trivalent, tetravalent or polyvalent cyclic carbonate monomers, the use of trivalent, tetravalent or polyvalent aldehyde monomers, or the use of trivalent, tetravalent or polyvalent amine monomers.
[0068] In one embodiment, the preparation of crosslinked PHUs includes combining divalent cyclic carbonates, divalent aldehyde monomers, divalent epoxide monomers, and diamine monomers of appropriate configuration. In non-limiting aspects, the preparation of such crosslinked PHUs (PHU-PI-epoxy) further includes the use of trivalent, tetravalent, or polyvalent cyclic carbonate monomers, the use of trivalent, tetravalent, or polyvalent aldehyde monomers, the use of trivalent, tetravalent, or polyvalent epoxide monomers, or the use of trivalent, tetravalent, or polyvalent amine monomers.
[0069] In certain embodiments, the preparation of the PHUs of the present disclosure further requires at least one catalyst, which may be a base or a nucleophile. In other embodiments, the at least one catalyst catalyzes the formation of urethane groups.
[0070] The method of preparing PHU disclosed herein includes, but is not limited to, the following embodiments.In one embodiment, the method comprises contacting at least one polyvalent cyclic carbonate monomer with at least one polyvalent amine monomer in a solvent, and converting the resulting material into a dry form of PHU, thereby preparing a composition comprising the PHU polymer.In another embodiment, the method comprises heating the melt mixture of at least one polyvalent cyclic carbonate monomer with at least one polyvalent amine monomer at high temperature, and cooling the resulting material to room temperature.In yet another embodiment, a method of reprocessing or utilizing PHU polymer for another purpose is disclosed.
[0071] In one embodiment, the method comprises contacting at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer in a solvent, and converting the resulting material into a dry form of PHU-PI, thereby preparing a composition comprising the PHU-PI polymer linked by hydroxyurethane bonds and imine bonds.In another embodiment, the method comprises heating a molten mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer at an elevated temperature, and cooling the resulting material to room temperature.In yet another embodiment, a method for reprocessing or utilizing PHU-PI polymers is disclosed.
[0072] In one embodiment, the method includes contacting at least one polyvalent cyclic carbonate monomer, at least one polyvalent aldehyde monomer, at least one polyvalent epoxide monomer, and at least one polyvalent amine monomer in a solvent, and converting the resulting material into a dry form of PHU, thereby preparing a composition comprising the PHU-PI-epoxy polymer linked by hydroxyurethane bonds, imine bonds, and -CN-CH2-C(OH)-. In another embodiment, the method includes heating a molten mixture of at least one polyvalent cyclic carbonate monomer, at least one polyvalent epoxide monomer, at least one polyvalent aldehyde monomer, and at least one polyvalent amine monomer at an elevated temperature, and cooling the resulting material to room temperature. In yet another embodiment, a method for reprocessing or otherwise utilizing a PHU-PI-epoxy polymer is disclosed.
[0073] In some embodiments, crosslinked PHU (PHU, PHU-PI, PHU-PI-epoxy) can be used as binder / resin for advanced composites such as talc, clay, carbon fiber (new, recycled, woven, chopped, or milled), and natural fibers (hemp, flax, etc.), graphene, carbon black, carbon nanotubes, glass fiber, and common and exotic fibrous composites. Such PHU composites are thermoformable, reworkable, and recyclable. In some embodiments, conductive composites can be prepared by using a combination of carbon fiber and conductive nanofillers (e.g., carbon black derivatives and graphene derivatives) as fillers in the PHU matrix.
[0074] Referring now to FIG. 1A, a method of forming a PHU according to an embodiment of the present disclosure is shown in schematic form. The method may include the formation of a cyclic carbonate from an epoxide and aminolysis of the cyclic carbonate. A hydroxyurethane bond is formed. High temperature and base catalysis may be applied to promote the hydroxyurethane formation and thus the polymerization process. The method provides for the incorporation of CO2 into the PHU, providing an environmentally friendly and sustainable approach to forming the PHU.
[0075] Now referring to FIG. 1B, carbamoyl transfer between free hydroxyl groups and carbamate groups is one of the mechanisms that allows the transition of PHU between malleable and non-malleable states and the recyclability of PHU. PHU inherently has free hydroxyl groups and carbamates in its polymer chain and therefore can undergo carbamoyl transfer. The kinetics of carbamoyl transfer can be adjusted through the addition of base catalysts (e.g., TBD or DMAP) or the application of heat. Carbamoyl transfer can occur within the same polymer chain and between separate polymer chains.
[0076] Referring now to Figure 1C, in the presence of excess monoalcohol components, the equilibrium shifts towards depolymerization, resulting in polymer chain scission and the formation of soluble oligomers or even monomer derivatives (e.g., multi-ols and polyhydric carbamates). Depolymerization of PHUs allows for the complete recovery of their chemical composition.
[0077] Referring now to Figure 1D, imine bonds can be incorporated into PHU by adding at least one polyaldehyde monomer in combination with at least one polycyclic carbonate monomer to form a PHU-PI hybrid, allowing for malleability of the PHU at lower temperatures, 80°C to 140°C. To tailor the mechanical properties of the PHU, polyepoxide monomers can also be combined with at least one polyaldehyde monomer and at least one polycyclic carbonate monomer to form a PHU-PI-epoxy hybrid containing hydroxyurethane, imine and -CN-CH2-C(OH)- bonds.
[0078] Now referring to FIG. 2A, examples of epoxides that can be converted to cyclic carbonate monomers through CO fixation include, but are not limited to, diglycidyl ether of bisphenol A (DGEBA), 4,4'-methylenebis(N,N-diglycidylaniline) (TGMDA), trimethylolpropane triglycidyl ether (TTE), biocompatible glycol diglycidyl ether (PEGDE), epoxidized soybean oil (ESBO), and limonene dioxide (LEP).
[0079] Referring now to FIG. 2B, examples of amines that can be used to polymerize polycyclic carbonates via aminolysis include, but are not limited to, hydrazine, diethylenetriamine (DETA), isophoronediamine (IPDA), tris(2-aminoethyl)amine (TREN), 4,4'-oxydianiline (ODA), and priamine (a 100% bio-based diamine), and aminopropyl-terminated polydimethylsiloxane (molecular weight = 150-30,000) (FIG. 2B).
[0080] As shown in FIG. 3A, the epoxide DGEBA can be converted to DGEBA-CO2 through reaction with CO2. A combination of tetrapropylammonium bromide (TPAB) and Ti(OiPr)4 can be used as a catalytic system. The product is: 1The DGEBA and crude DGEBA-CO2 products can be characterized by H NMR spectroscopy. 1 Comparison of the H NMR spectra indicates the high purity of the crude product even in the absence of a purification process.
[0081] In another embodiment, PHU films, PHU-PI films, or PHU-PI-epoxy films were prepared by pre-dissolving the monomers in dimethylformamide (DMF) and adding the resulting solutions together in an open container in an oven at 120° C. When the DMF evaporated, the polymer film was formed.
[0082] As shown in Table 1, various PHU polymers, PHU-PI polymers, and PHU-PI-epoxy polymers could be formed when mixtures of divalent DGEBA-CO2, various amounts of terephaldehyde (TPA) and DGEBA, diamine DETA or preamine, and triamine TREN in solvent were heated at 120°C for 10-15 hours. The freshly prepared polymer film samples were heat pressed at 120°C for another 1-2 hours. After cooling to room temperature (20°C-25°C), the films were characterized by stress-strain experiments. The tensile modulus (Young's modulus) of these PHU-related polymers was in the range of about 2.6GPa to 5.2GPa. In one embodiment, the curves in FIG. 3C show typical stress-strain performance of the PHU-PI polymer: Young's modulus about 4.5 GPa to 4.9 GPa, break stress about 90 MPa to 108 MPa, and elongation at break about 3% to 4%.
[0083] In some embodiments, the chemical composition, functional group content, and free end groups of PHU could be characterized by FTIR and NMR spectroscopy. The mechanical properties (tensile modulus, strength, and elongation) of PHU could be evaluated by uniaxial tensile testing using an Instron. The glass transition temperature of PHU could be measured using Dynamic Mechanical Analysis (DMA). The activation temperature of carbamoyl group transfer could be determined through temperature-dependent stress relaxation experiments. The bulk stress relaxation of PHU under various temperatures could be measured using DMA. Thermogravimetric analysis (TGA) could be performed to evaluate the thermal stability. Swelling tests in various organic solvents and in water could be performed to evaluate their chemical stability.
[0084] Carbamoylation occurs through the exchange of carbamate groups with free pendant hydroxyl groups in the absence or presence of base. PHU contains both free hydroxyl groups and hydroxyurethane bonds, and thus undergoes carbamoylation, which contributes to its malleability and recyclability. The kinetics of the bond exchange are important for achieving fast stress relaxation and short rework time. The kinetic profile of carbamoylation and its possible side reactions could be evaluated using small molecule model compounds with various electronic and steric features. The reaction conditions, including catalyst and temperature, also play an important role in determining the kinetic relaxation behavior of PHU. PHU malleability is possible at temperatures between 80°C and 250°C.
[0085] In some embodiments, imine bonds can be incorporated into PHU by using at least one polyvalent aldehyde monomer in combination with at least one polyvalent cyclic carbonate monomer as the reactive counterpart of the amine monomer to form a hybrid polymer of PHU and polyimine (PI) (PHU-PI). When imine bonds are incorporated into PHU, its malleability can be increased and made possible at lower temperatures (80°C to 140°C).
[0086] In an embodiment, PHU, PHU-PI, and PHU-PI-epoxy can be recycled when the product of the recycling process can be reused to produce PHU polymer, PHU-PI polymer, PHU-PI-epoxy polymer with similar properties to the original polymer. In an embodiment, as shown in FIG. 4, PHU produced from DGEBA-CO2 and TREN was depolymerized in ethanol. Potassium carbonate (K2CO3) was added as a catalyst. The depolymerization occurs through carbamoyl transfer between the hydroxyurethane group in the polymer chain and ethanol with a primary hydroxy group, which results in polymer chain scission and molecular weight reduction. The PHU can be converted into soluble oligomers and further into small molecules such as DGEBA-4OH, a multi-hydroxy compound, and 3Cbm-TREN, a multivalent carbamate. Carbamoyl transfer between DGEBA-4OH and 3Cbm-TREN with removal of ethanol can form PHU with a chemical composition similar to the original PHU. DGEBA-4OH could also be converted to DGEBA through a one-step dehydration. 3Cbm-TREN could be converted to 3Me-TREN through a one-step reduction. These small molecules can be used as starting materials in the preparation of other materials.
[0087] In one embodiment, the present invention provides a method for producing carbon fiber reinforced composites (CFRCs) produced from crosslinked PHU polymers, crosslinked PHU-PI polymers, and crosslinked PHU-PI-epoxy polymers. There are two methods for producing PHU-containing CFRCs: liquid-based and semi-solid-based. In the former method, a liquid monomer combination is first infiltrated into the carbon fibers and then cured to form a solid composite. In the latter method, the fibers are first combined with a crosslinked polymer resin to form a layer of fiber-matrix mixture (known as a "prepreg"). Due to the malleability of the crosslinked PHU polymers, crosslinked PHU-PI polymers, and crosslinked PHU-PI-epoxy polymers, the CFRC prepregs produced from the PHU polymers, PHU-PI polymers, and PHU-PI-epoxy polymers have an infinite shelf life. The prepregs can be used later to form laminates with desired layups and shapes through vacuum bag molding or compression molding.
[0088] In another embodiment, these composite materials can be prepared in ratios ranging from 30:70 fiber:resin by weight to 70:30 fiber:resin by weight. In yet another embodiment, these materials can be prepared in ratios ranging from 10:90 fiber:resin by weight to 90:10 fiber:resin by weight.
[0089] In one embodiment, the present invention provides a liquid-based method for the preparation of CFRCs from DGEBA-CO2 and TREN, as shown in FIG. 5A. A sheet of woven carbon fiber was placed in a solution of DGEBA-CO2 and TREN in DMF in an open container. The setup was placed at 100° C. in a fume hood. When the DMF evaporated, a layer of composite was formed. In another embodiment, a combination of milled recycled carbon fiber and conductive carbon black was used in place of the woven carbon fiber sheet. The resulting composite has a conductivity in the range of 500 s / m to 3000 s / m.
[0090] According to some embodiments, the composites produced from PHU polymer, PHU-PI polymer, and PHU-PI-epoxy polymer may be malleable and thermoformable, allowing for reworking of the composite. The composites in embodiments may be cut, bent, or otherwise shaped so that the composite assumes a suitable shape for its intended use. The resulting shaped composite may then be heated above its transition temperature in the range of 80°C to 250°C for at least 3 minutes, or for a period in the range of 1 hour to 4 hours. After cooling to a temperature below its transition temperature, the shape may be retained without the temporary reinforcement used in the molding process. The thermoforming process may be repeated at least once. The composite may be molded multiple times by repeating the heating and cooling cycles, as shown in FIG. 5B.
[0091] In an embodiment, the composites can be recycled in an efficient closed-loop process, and the chemical components and fibers produced in the recycling process can be reused for their original purpose. In an embodiment, composites produced from carbon fiber fabric sheets and PHU, PHU-PI, or PHU-PI-epoxy can be recycled by depolymerizing the PHU polymer. The depolymerization occurs mainly through carbamoyl transfer between the urethane groups in the polymer chain and alcohols with primary hydroxyl groups, which results in polymer chain scission and molecular weight reduction. The PHU can be converted into soluble oligomers and even small molecules. These chemical products from the recycling process can be converted into PHU, PHU-PI, or PHU-PI-epoxy, or purified into chemical feedstocks that can be used for other purposes. The carbon fiber fabric can be recovered from the recycling solution and reused to produce composites.
[0092] In some embodiments, the disclosed PHU products (PHU, PHU-PI, or PHU-PI-epoxy) have at least some or all of the following advantages: (1) unlike traditional polyurethanes (PU), the production of these polymers does not rely on isocyanate chemistry, which is associated with high toxicity; (2) they have mechanical and thermal properties comparable to or superior to traditional PU thermosets, but are reworkable and recyclable; (3) when used as a polymer matrix in fiber-reinforced composites, they can have mechanical properties comparable to typical CFRCs produced from thermosets, but with excellent reworkability and full recyclability of all of their chemical components and fibers. These advantages are achieved by the incorporation of dynamic hydroxyurethane crosslinks in the presence or absence of dynamic imine bonds, which can be broken and reformed under applied stimuli (i.e., catalyst and temperature). PHU-related products produced from CO2-derived monomers can reduce carbon footprints and contribute to a "circular economy."
[0093] The present disclosure may be further illustrated by the following:
[0094] Item 1: A composition comprising a polyhydroxyurethane (PHU) polymer prepared from a reaction system comprising a polyvalent cyclic carbonate monomer and a polyvalent amine monomer.
[0095] Item 2: The composition according to item 1, wherein the molar equivalent ratio of total cyclic carbonate groups to total amine groups in the reaction system is about 1:1.
[0096] Item 3: The composition of any of the above items, further comprising at least one fiber.
[0097] Item 4. The composition of item 3, wherein the at least one fiber is a carbon fiber.
[0098] Item 5: A composite material comprising the composition according to any one of the preceding items, the composite material being prepared by curing the composition according to any one of the preceding items.
[0099] Item 6: The composition according to any of the preceding items, wherein the polyhydroxyurethane polymer is not malleable in a dry form at room temperature, and the polyhydroxyurethane polymer becomes malleable when the polyhydroxyurethane polymer is in contact with a catalyst or when the polyhydroxyurethane polymer is heated to a temperature between 70°C and 250°C.
[0100] Item 7: A composition comprising a hybrid polymer (PHU-PI) of polyhydroxyurethane (PHU) and polyimine (PI) prepared from a reaction system containing a polyvalent cyclic carbonate monomer, a polyvalent aldehyde monomer, and a polyvalent amine monomer.
[0101] Item 8: The composition according to item 7, wherein the molar equivalent ratio between the total of the cyclic carbonate groups and aldehyde groups in the reaction system and the total amine groups is about 1:1 ((cyclic carbonate + aldehyde):amine is about 1:1).
[0102] Item 9: The composition according to any one of items 7 to 8, further comprising at least one type of fiber.
[0103] Item 10. The composition of item 9, wherein the at least one fiber is a carbon fiber.
[0104] Item 11: A composite material comprising the composition according to any one of items 9 to 10, the composite material being prepared by curing the composition according to any one of items 9 to 10.
[0105] Item 12: The composition according to any one of items 7 to 11, wherein the polyhydroxyurethane (PHU) and polyimine (PI) hybrid polymer (PHU-PI) is not malleable in a dry form at room temperature, and the PHU-PI hybrid polymer becomes malleable when the PHU-PI hybrid polymer is in contact with a catalyst or when the PHU-PI hybrid polymer is heated to a temperature between 70°C and 250°C.
[0106] Item 13: A composition comprising a hybrid polymer (PHU-PI-epoxy) of polyhydroxyurethane (PHU), polyimine (PI), and epoxy resin, prepared from a reaction system containing a polyvalent cyclic carbonate monomer, a polyvalent aldehyde monomer, a polyvalent epoxide monomer, and a polyvalent amine monomer.
[0107] Item 14: The composition according to item 13, wherein the molar equivalent ratio between the total of cyclic carbonate groups + aldehyde groups + epoxide and the total amine groups in the reaction system is about 1:1 ((cyclic carbonate + aldehyde + epoxide):amine is about 1:1).
[0108] Item 15: The composition according to any one of items 13 to 14, further comprising at least one type of fiber.
[0109] Item 16. The composition of item 15, wherein the at least one fiber is a carbon fiber.
[0110] Item 17: A composite material comprising the composition according to any one of items 13 to 16, the composite material being prepared by curing the composition according to any one of items 13 to 16.
[0111] Item 18: The composition according to any one of items 13 to 17, wherein the hybrid polymer of polyhydroxyurethane (PHU), polyimine (PI) and epoxy resin (PHU-PI-epoxy) is not malleable in a dry form at room temperature, and the PHU-PI-epoxy hybrid polymer becomes malleable when the PHU-PI-epoxy hybrid polymer is in contact with a catalyst or when the PHU-PI-epoxy hybrid polymer is heated to a temperature between 70°C and 250°C.
[0112] Item 19: a) heating the composite material in sheet form to an elevated temperature; b) compressing the material from step (a); and c) cooling the material from step (b) to room temperature. 19. A method for reshaping the composition according to any one of items 1 to 18, comprising:
[0113] Item 20: a) contacting the polyhydroxyurethane polymer with a liquid to form a soluble material; and b) converting the soluble material into a dry or small molecule pure form of the polyhydroxyurethane polymer. 19. A method for recycling a composition according to any one of items 1 to 18, comprising:
[0114] Item 21: a) contacting the composition with a liquid to form a soluble material; b) separating at least one fiber from the soluble material; and c) converting the soluble material into a dry or small molecule pure form of the polyhydroxyurethane polymer. 19. A method for recycling a composition according to any one of items 1 to 18, comprising:
[0115] Item 22: The composition according to item 5, wherein the weight ratio between the carbon fiber and the polymer is 10:90 to 70:30.
[0116] Item 23: A process for preparing a polyvalent cyclic carbonate monomer, comprising: reacting the epoxy precursor with CO2 in the presence of a catalyst wherein the catalyst is a combination of Ti(OiPr)4 and TPAB or a combination of Ti(OiPr)4 and tetrabutylammonium bromide.
[0117] Item 24: The process of item 23, wherein the polyvalent cyclic carbonate monomer is DGEBA-CO2.
[0118] Item 25: The process of item 23, wherein the epoxy precursor is a diglycidyl ether of bisphenol A (DGEBA). EXAMPLES
[0119] (Example) The following examples are provided to illustrate certain embodiments of the present disclosure and to illustrate features and advantages of those embodiments, but are not intended to limit its scope. Instead, the examples will guide those of ordinary skill in the art in understanding and applying the inventive features of the present disclosure.
[0120] Example 1 Synthesis of DGEBA-CO2 (FIG. 3A): A solution of DGEBA (20 g, 58.5 mmol), Ti(OiPr)4 (166 mg, 0.58 mmol), and TPAB (154 mg, 0.58 mmol) in DMF (10 mL) was added to a vial. Dry ice (20 g) was added to a pressure vessel and the vial was placed on top of the dry ice. The pressure vessel was sealed and heated at 100 °C in an oil bath. The vessel pressure gauge indicated that the internal pressure was around 400 Psi-700 Psi. After heating at 100 °C for 6-10 h, the reaction was cooled to room temperature and the internal pressure was released. NMR of the crude product shows clean DGEBA-CO2 product with a small amount of TPAB. The reaction mixture was dissolved in hot DMF (approximately 30 mL) and the product was recrystallized. The white solid was filtered and dried in an oven at 70° C. to give DGEBA-CO2 (18 g-22 g, 74%-89%): 1 H NMR (300 MHz, chloroform-d) δ 7.20 - 7.11 (m, 4H), 6.86 - 6.76 (m, 4H), 5.02 (dddd, J = 8.1, 5.9, 4.3, 3.6 Hz, 2H), 4.67 - 4.48 (m, 4H), 4.29 - 4.06 (m, 4H), 1.64 (s, 6H). 1 H-NMR spectra were obtained on a Burker-300 Ultrashield NMR instrument.
[0121] Example 2 Synthesis of PHU (Figure 3B): DGEBA-CO2 (1.0 g) and TREN (228 mg) were mixed in DMF (5 mL). The clear solution was poured into a Petri dish and heated at 100 °C for 2 h. A PHU film was formed. It was hot pressed at 100 °C for another 3-4 h. Its Young's modulus was 2.6 GPa, the break stress was about 73 MPa, and the elongation at break was about 3%-4% (Table 1, PHU). [Table 1]
[0122] Example 3 Synthesis of PHU-PI: DGEBA-CO2 (2.00 g, 4.67 mmol) and TPA (63 mg, 0.477 mmol) were dissolved in DMF (5 mL). To the homogenous solution, DETA (144 mg, 1.40 mmol) was added dropwise with stirring, followed by TREN (319 mg, 2.18 mmol). The yellow-orange solution was poured into a PTFE Petri dish and heated at 120 °C for 18 h to form a yellow film (2.52 g, 100%). Its Young's modulus was 4.9 GPa, its break stress was about 108 MPa, and its elongation at break was about 3%-4% (Figure 3C, Table 1, PHU-PI-5).
[0123] Example 4 Synthesis of PHU-PI-Epoxy: DGEBA-CO2 (1.50 g, 3.50 mmol), DGEBA (511 mg, 1.50 mmol), and TPA (67 mg, 0.50 mmol) were dissolved in DMF (10 mL). To the homogenous solution, DETA (155 mg, 1.50 mmol) was added dropwise with stirring followed by TREN (341 mg, 2.33 mmol). The yellow-orange solution was poured into a PTFE Petri dish and heated at 120 °C for 18 h to form a yellow film (2.51 g, 98%). Its Young's modulus was 5.2 GPa (Table 1, PHU-PI-Epoxy).
[0124] Example 5 Recycling of PHU polymer (Figure 4): A piece of PHU polymer film (200 mg) was immersed in a suspension of K2CO3 (100 mg) in ethanol (10 mL). The mixture was heated at 100 °C for 10 h with stirring. The PHU film was completely dissolved. The mixture was filtered and the filtrate was concentrated to give 4OH-DGEBA and 3Cbm-TREN.
[0125] Example 6 Preparation of CFRC sheets from carbon fiber fabric (Figure 5A): A piece of carbon fiber fabric (1.17 g, FibreGlast, 3k fiber) was immersed in a solution of DGEBA-CO2 (500 mg), TREN (114 mg) in DMF (3 mL). The mixture was heated at 100 °C for 2 h. The formed film was hot pressed at 100 °C for another 3-4 h to obtain a composite sheet. The tensile properties of the prepared composite sheet were measured through uniaxial tensile tests. Its Young's modulus was 50 GPa-60 GPa, the break stress was 600 MPa-700 MPa, and the break elongation was about 1%-2%.
[0126] Example 7 Recycling of CFRC (FIG. 5C): A CFRC sheet (400 mg) was immersed in a suspension of K2CO3 (100 mg) in ethanol (10 mL). The mixture was heated at 100 °C for 10 h with stirring. The PHU matrix was completely dissolved. The carbon fibers were removed from the solution and dried for reuse. The remainder of the mixture was filtered and the filtrate was concentrated to obtain 4OH-DGEBA and 3Cbm-TREN.
[0127] Example 8 Preparation of conductive CFRC sheets from recycled milled carbon fibers (Figure 6): A mixture of milled recycled carbon fibers (rCF, 600 mg, Zoltek, recycled milled fibers, 150 μm length) and carbon black Super C45 (25 mg) in DMF (3 mL) was sonicated for 20 min with a probe sonicator (Sonics, VCX 750). In a separate vial, DGEBA-CO2 (500 mg), TREN (80 mg), and DETA (36 mg) were mixed in DMF (2 mL). The two mixtures were then mixed and poured into a Petri dish (6 cm diameter). The mixture was heated at 100 °C for 10 h. A black sheet of the composite was formed. The electrical conductivity of the composite was measured using a four-point probe and found to be between 1850 s / m and 2630 s / m. The tensile properties of the prepared PHU polymer were measured from uniaxial tensile tests. Its Young's modulus was 13.5 GPa, its breaking stress was about 70 MPa, and its breaking elongation was about 0.8%.
Claims
1. A composition comprising a polyhydroxyurethane (PHU) polymer prepared from a reaction system comprising a polyhydric cyclic carbonate monomer and a polyhydric amine monomer.
2. 2. The composition of claim 1, wherein the molar equivalent ratio of total cyclic carbonate groups to total amine groups in the reaction system is about 1:
1.
3. The composition of claim 1 further comprising at least one fiber.
4. The composition of claim 3 , wherein the at least one fiber is a carbon fiber.
5. A composite material comprising the composition of claim 3, the composite material being prepared by curing the composition of claim 3.
6. 2. The composition of claim 1, wherein the polyhydroxyurethane polymer is not malleable in a dry form at room temperature, and the polyhydroxyurethane polymer becomes malleable when the polyhydroxyurethane polymer is in contact with a catalyst or when the polyhydroxyurethane polymer is heated to a temperature between 70°C and 250°C.
7. A composition comprising a hybrid polymer (PHU-PI) of polyhydroxyurethane (PHU) and polyimine (PI) prepared from a reaction system containing a polyvalent cyclic carbonate monomer, a polyvalent aldehyde monomer, and a polyvalent amine monomer.
8. 8. The composition of claim 7, wherein the molar equivalent ratio between the total of cyclic carbonate and aldehyde groups and the total amine groups in the reaction system is about 1:1 ((cyclic carbonate+aldehyde):amine is about 1:1).
9. The composition of claim 7 further comprising at least one fiber.
10. 10. The composition of claim 9, wherein the at least one fiber is a carbon fiber.
11. 10. A composite material comprising the composition of claim 9, the composite material being prepared by curing the composition of claim 9.
12. 8. The composition of claim 7, wherein the polyhydroxyurethane (PHU) and polyimine (PI) hybrid polymer (PHU-PI) is not malleable in dry form at room temperature, and the PHU-PI hybrid polymer becomes malleable when the PHU-PI hybrid polymer is in contact with a catalyst or when the PHU-PI hybrid polymer is heated to a temperature between 70° C. and 250° C.
13. A composition comprising a hybrid polymer (PHU-PI-epoxy) of polyhydroxyurethane (PHU), polyimine (PI), and epoxy resin, prepared from a reaction system containing a polyvalent cyclic carbonate monomer, a polyvalent aldehyde monomer, a polyvalent epoxide monomer, and a polyvalent amine monomer.
14. 14. The composition of claim 13, wherein the molar equivalent ratio between the total of cyclic carbonate groups + aldehyde groups + epoxide groups and the total amine groups in the reaction system is about 1:1 ((cyclic carbonate + aldehyde + epoxide):amine is about 1:1).
15. The composition of claim 13 further comprising at least one fiber.
16. 16. The composition of claim 15, wherein the at least one fiber is a carbon fiber.
17. 16. A composite material comprising the composition of claim 15, the composite material being prepared by curing the composition of claim 15.
18. 14. The composition of claim 13, wherein the polyhydroxyurethane (PHU), polyimine (PI) and epoxy resin hybrid polymer (PHU-PI-epoxy) is not malleable in a dry form at room temperature, and the PHU-PI-epoxy hybrid polymer becomes malleable when the PHU-PI-epoxy hybrid polymer is in contact with a catalyst or when the PHU-PI-epoxy hybrid polymer is heated to a temperature between 70° C. and 250° C.
19. a) heating the composite material in sheet form to an elevated temperature; b) applying pressure to the material from step (a); and c) cooling the material from step (b) to room temperature. A method for reforming the composition of claim 4 comprising:
20. a) contacting the polyhydroxyurethane polymer with a liquid to form a soluble material; and b) converting the soluble material into a dry or small molecule pure form of the polyhydroxyurethane polymer.
2. A method for recycling the composition of claim 1, comprising:
21. a) contacting the composition with a liquid to form a soluble material; b) separating at least one fiber from the soluble material; and c) converting the soluble material into a dry or small molecule pure form of the polyhydroxyurethane polymer.
5. A method for recycling the composition of claim 4, comprising:
22. The composition of claim 5, wherein the weight ratio between the carbon fibers and the polymer is from 10:90 to 70:
30.
23. 1. A process for preparing a polyvalent cyclic carbonate monomer comprising: The epoxy precursor is reacted with CO in the presence of a catalyst. 2 Reacting with The catalyst comprises Ti(OiPr) 4 and TPAB or Ti(OiPr)4 and tetrabutylammonium bromide.
24. The polyvalent cyclic carbonate monomer is DGEBA-CO 2 24. The process of claim 23, wherein
25. 24. The process of claim 23, wherein the epoxy precursor is a diglycidyl ether of bisphenol A (DGEBA).